Efficacy and safety of hepatic arterial infusion chemotherapy combined with programmed cell death protein-1 antibody and lenvatinib for advanced hepatocellular carcinoma - Xu, Yongkang; Fu, Shumin; Mao, Ye; Huang, Shenglan; Li, Dan; Wu, Jianbing (Frontiers in Medicine, 2022)
Background The purpose of the study was to assess the efficacy and safety in patients with advanced hepatocellular carcinoma (HCC) who are undergoing hepatic arterial infusion chemotherapy (HAIC) combined with programmed cell death protein-1 (PD-1) antibody and lenvatinib. Methods We retrospectively evaluated 61 patients treated with HAIC combined with PD-1 antibody and lenvatinib at the Second Affiliated Hospital of Nanchang University between September 2020 and January 2022 for advanced HCC. We analyzed tumor response, progression free survival (PFS), and treatment-related adverse events (TRAEs). Results The objective response rate (ORR) was 36.1% (RECIST 1.1)/57.4% (mRECIST) and the disease control rate (DCR) was 82.0%. The overall median PFS was 6.0 months, 6.7 months for first-line treatment, and 4.3 months for second-line treatment. The most common TRAEs were neutropenia (50.8%), abdominal pain (45.9%), and aspartate aminotransferase increase (39.3%). Conclusion Hepatic arterial infusion chemotherapy combined with PD-1 antibody and lenvatinib is effective in the treatment of advanced HCC, and the TRAEs are generally controllable.